PERAN KEPEMIMPINAN SEBAGAI PERWUJUDAN ENTREPRENEURSHIP KRISTEN DI GEREJA TORAJA JEMAAT TIATIRA TAMBUNAN - Christian Briand Samulung; Dewindilia Saratu’; Risna Sampe Allo; Selomita; Yelwisda Lande’ (Jurnal Salome : Multidisipliner Keilmuan, 2025)
Christian entrepreneurship is a creative act made possible by the creative impulse given by God to every believer. Christian leaders must have innovative and creative abilities in leading the congregation to transform various difficulties into opportunities. They must be able to develop the potential of creativity and innovation of congregation members, as well as create useful jobs for congregation members. Thus, the congregation can become a center for driving a sustainable local economy and make a positive contribution to the welfare of society. This study explores the role of leadership in realizing the spirit of Christian entrepreneurship within the congregation. Using a qualitative approach, this study examines how Christian leadership can be a catalyst in shaping an organizational culture that encourages innovation, service, and spiritual growth. Through an analysis of the literature and case studies, this study highlights the importance of leadership based on Christian values in guiding the congregation in practicing entrepreneurial principles that are in accordance with Christian teachings. The findings of this study indicate that leadership rooted in Christian principles can influence the transformation of the congregation towards a balance between achieving spiritual goals and financial sustainability.